PERAN ORANG TUA DALAM MENSTIMULASI KEMAMPUAN MENGENAL ABJAD ANAK KELOMPOK A DI TKS IT UNGGUL SRIWIJAYA PADA MASA PANDEMI COVID-19 - Mei First Veronica Riana (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
This study aims to find out how the role of parents in stimulating the ability to recognize the alphabet in group A children at TKS IT Unggul Sriwijaya during the covid-19 pandemic. This study uses a quantitative descriptive research with a research sample of 15 respondents from group A's guardians of students at TKS IT Unggul Sriwijaya. The data collection that the researchers used were questionnaires and interviews. The data analysis technique used quantitative descriptive analysis. The indicators in this study include: 1) The role of parents as facilitators with a percentage value of 64%, 2) The role of parents as motivators with a percentage value of 78%, 3) The role of parents as mentors/teachers with a percentage of 88%. The results showed that the role of parents in stimulating the ability to recognize the alphabet of group A children at TKS IT Unggul Sriwijaya was 77% or in the Good (Good) category. The indicator of the role of parents in stimulating the ability to recognize the alphabet of group A children at TKS IT Unggul Sriwijaya, the highest percentage is the role of parents as mentors/teachers, parents have carried out their duties well, namely often (3-5 times a week) or even always ( 6-7 times a week) explains the difference between each alphabet, teaches how to write the alphabet, while the indicator with the lowest percentage is the role of parents as facilitators, most parents have provided facilities such as providing posters with pictures of the alphabet, showing videos containing the introduction of the alphabet, and reading story books about the alphabet but still rarely or sometimes like 1-2 times a week. Keywords: Role of Parents, Stimulation, Ability to Recognize Letters